Participate (or not) in international trade fairs? Decision factors of Portuguese managers - Santos, José de Freitas (2014)
Portugal is a small economy, with an open domestic market that needs competitive exporters to prosper. Trade fairs are an international promotion tool that can be used by firms when considering export development and expansion. This study identifies and evaluates the critical factors that influenced the decision making process of Portuguese SME’s (Small and Medium-Sized Enterprises) managers to participate (or not) in international trade fairs. The results indicate that the firm’s critical decisions factors to select an international trade fair were value for money and the stand (location, typology and size)